2008
DOI: 10.1016/j.jretconser.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of brand credibility on customer loyalty

Abstract: Customer churn is an ever-growing issue in the relational services sector (e.g., retail banking, telecommunications), where business models ultimately depend upon long-term relationships with customers as the basis for profitability. Businesses in this sector have tended to view satisfaction and service quality as the key tools for increasing customer retention. The present study investigates the important additional role of the brand in managing the churn of current customers of relational services. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
244
1
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(275 citation statements)
references
References 82 publications
18
244
1
12
Order By: Relevance
“…The two dimensions of brand credibility (Erdem & Swait, 2004) are used by many recent brand credibility related studies (e.g., Alam et al, 2012;Kemp & Bui, 2011;Spry et al, 2011;Sweeney & Swait, 2008;Wang & Yang, 2010) to measure the construct of brand credibility. Thus, this study also considers trustworthiness and expertise as dimensions of brand credibility as replication to existing literature (see Figure 2).…”
Section: Brand Credibilitymentioning
confidence: 99%
“…The two dimensions of brand credibility (Erdem & Swait, 2004) are used by many recent brand credibility related studies (e.g., Alam et al, 2012;Kemp & Bui, 2011;Spry et al, 2011;Sweeney & Swait, 2008;Wang & Yang, 2010) to measure the construct of brand credibility. Thus, this study also considers trustworthiness and expertise as dimensions of brand credibility as replication to existing literature (see Figure 2).…”
Section: Brand Credibilitymentioning
confidence: 99%
“…A confiança do consumidor manifesta-se pela expectativa de que a empresa se comportará de maneira competente, altruís-ta e honesta no relacionamento (Sirdeshmukh, Singh, & Sabol, 2002;Sweeney & Swait, 2008 Não há um consenso quanto à definição e operacionalização da lealdade, contudo grande parte das pesquisas tem sido pautada por duas abordagens. Na abordagem comportamental, a lealdade é expressa por meio dos comportamentos passados de compras do consumidor.…”
Section: Referencial Teóricounclassified
“…They reported that brand credibility could decrease price sensitivity and although the direction of the effect was the same, the magnitude of brand credibility's impact on consumer choices and price sensitivity could be different across product categories, as a function of product category characteristics, which impact potential consumer uncertainty and consumer sensitivity to such uncertainty. Sweeney and Swait (2008) studied the important additional impact of the brand in managing the churn of current customers of relational services. They tried to find out whether the credibility of the brand could underlay the effect that the brand could play in this process.…”
Section: Introductionmentioning
confidence: 99%